Diferencia significativa en el pago de impuestos de rentas de quinta categoría con empresas de tercera categoría en el Perú – 2022 - Murrieta Davila, Andres (2024)
The general objective of the thesis is to determine the difference that exists in the payment of fifth category income taxes with third category companies in Peru, 2022, according to the research topic, the significant difference in the payment of fifth category income taxes with third category companies in Peru - Year 2022. The research is descriptive, correlational and non-experimental; the population is made up of thirty people, which are composed of 8 teachers of the Unap, between associates and principals, and 7 doctors of the hospital of Iquitos, 8 entrepreneurs of Mype Tributario and 7 entrepreneurs of the General Regime and The sample was selected non-randomly and by convenience, and is constituted by the entire population for being very small. The technique for data collection was the interviews through questionnaires were made with 25 questions that were our instruments, the questions were the following: do you agree with your fifth category discounts; do you agree that all income is discounted; do you agree that your fifth category tax is not discounted, in the statistics we used the mean, standard deviation and variance to quantify the dispersion or variability of a set of data with respect to its mean. Conclusion: There is a difference in the payment of fifth category taxes with third category companies in Peru, 2022.